2016
DOI: 10.2169/internalmedicine.55.5544
|View full text |Cite
|
Sign up to set email alerts
|

Memory Loss and Frontal Cognitive Dysfunction in a Patient with Adult-onset Neuronal Intranuclear Inclusion Disease

Abstract: Neuronal intranuclear inclusion disease (NIID) is an uncommon progressive neurodegenerative disorder. Adult-onset NIID can result in prominent dementia. We herein describe the case of a 74-year-old man who presented with dementia, cerebellar ataxia, neuropathy, and autonomic dysfunction. Diffusion-weighted imaging showed hyperintensity of the corticomedullary junction. Fluid-attenuated inversion recovery images showed frontal-dominant white matter hyperintensity. NIID was diagnosed from the presence of intranu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
0
31
1
Order By: Relevance
“…One previous case reported a reduced level of consciousness and recurrent vomiting, though the patient's symptoms continued to progress, which differs from our case [11]. Although multiple reversible encephalitic attacks have been described in case reports previously, some symptoms such as dysarthria recovered completely afterwards, but there were some residual symptoms such as impaired memory and word recall, saccadic pursuit eye movements and mild weakness of the left lower extremity [12][13][14]. In this case, we report a patient with NIID who presented with recurrent loss of consciousness and cognitive impairment that completely recovered within a short time.…”
Section: Discussioncontrasting
confidence: 65%
“…One previous case reported a reduced level of consciousness and recurrent vomiting, though the patient's symptoms continued to progress, which differs from our case [11]. Although multiple reversible encephalitic attacks have been described in case reports previously, some symptoms such as dysarthria recovered completely afterwards, but there were some residual symptoms such as impaired memory and word recall, saccadic pursuit eye movements and mild weakness of the left lower extremity [12][13][14]. In this case, we report a patient with NIID who presented with recurrent loss of consciousness and cognitive impairment that completely recovered within a short time.…”
Section: Discussioncontrasting
confidence: 65%
“…Of the diagnosis of the 50 cases with NIID reviewed, 20 were confirmed by skin biopsy, 15 by autopsy, 10 by rectal biopsy, 1 by colon biopsy, 1 by both the skin and the rectal biopsy, and 3 reports made no mention of the pathology (Table ) . There were 31 patients with MRI records, including 23 patients with brain atrophy (23/31, 74.19%).…”
Section: Resultsmentioning
confidence: 99%
“…However, abnormal signals in the above regions were not displayed on the DWI sequence. This imaging change was considered to be associated with the presence of chronic persistent hypoperfusion‐induced cytogenic and angiogenic edema in the patient's brain (Araki et al, ). A previous study confirmed that symmetrically distributed strip‐shaped high‐intensity signals in bilateral fronto‐occipital‐parietal cortical‐medullary junction on DWI tended to extend backwards as the disease progressed and did not disappear over time (Sone et al, ).…”
Section: Discussionmentioning
confidence: 99%